Profile of Fungal and Bacterial Infections in Inguinal Erythrosquamous Dermatoses - Irma Tarida Listiyawati; Sunarso Suyoso; Rahmadewi Rahmadewi (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Erythrosquamous dermatoses are diseases of the skin, characterized with the erythematous changing accompanied with scales. Usually, the patients were treated with antifungal and antibiotic, but there were no data to support this therapy. Purpose: To describe the profile of fungal and bacterial infections in erythrosquamous dermatoses. Methods: This is a descriptive cross-sectional study in patient with inguinal erythrosquamous dermatoses in Dermatology and Venereology Outpatient Department, Dr. Soetomo General Hospital 2016. Subjects have been collected through consecutive sampling, and the amount of subject were determined  as total sampling from May – August 2016 Results: The profile of fungal infections were tinea kruris (57.14%) and intertriginous candidiasis (9.52%). Fungal infections as a trigger were seborrheic dermatitis (14.29%) and erythema intertrigo (14.29%). Profile of bacterial infections were erythrasma (4.76%). Result of fungal culture were T. mentagrophytes (52.38%), C. parapsilosis (9.52%), S. ciferii (4.76%), C. albicans (4.76%), T. inkin (4.76%), Malaszesia spp (9.52%), and negative result (14.28%). Result of gram positive bacterial culture were S. aureus (38.10%), S. epidermidis (9.52%), S. lentus, S. haemolyticus, S. hominis 4.76%. Mixed gram positive bacteria were S. aureus-S. haemolyticus dan S. lentus-E. faecalis 4.76%. Gram positive and gram negative bacteria were S. aureus-A. baumanii, S. aureus-S. haemolyticus-A. baumanii 4.76% each. Gram negative bacteria were A. baumanii  and  K. pneumoniae 4.76% each and  contamination 9.52%. Conclusion: The profile of fungal and bacterial infections in inguinal erythrosquamous dermatoses mostly were tinea cruris. The result of fungal culture mostly were T. mentagrophytes. The result of bacterial culture mostly were gram positive bacteria, consist of S. aureus, S. epidermidis, S. lentus, S. haemolyticus, S. hominis, E. faecalis.